Sosialisasi Buku Lahan Berkah dan Berdaya: Menjaga Ketahanan Pangan dan Kesejahteraan Umat - Ariesman M. (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
The socialization of the book Blessed and Empowered Land with the theme Maintaining Food Security and Welfare of the People was carried out online via Zoom webinar on Saturday, September 30, 2023. This activity was attended by 54 participants consisting of Wahdah Islamiyah cadres and administrators, agricultural instructors, and the general public. The socialization activity was divided into two sessions, namely a material presentation session, and a discussion session. In the material presentation session, the concept of strategies for revitalizing and optimizing the function of land to be more productive is discussed, to achieve food security and welfare of the people. In the discussion session, participants can ask questions and discuss with the resource persons. The results of the activity showed that the online socialization of the book Tanah Berkah dan Berdaya succeeded in increasing the understanding of cadres, Wahdah Islamiyah administrators, and the community about the importance of maintaining food security and the welfare of the people. Activity participants can understand the concepts and strategies for reviving and optimizing land functions to make them more productive. In conclusion, online socialization of the book Tanah Berkah dan Berdaya is an effective effort to increase public understanding of the importance of maintaining food security and the welfare of the people.